The origin of the Christian faith - Funda, Otakar (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
The paper presents O. A. Funda’s “Maranatha” hypothesis, first published in Czech in 2007 (Ježíš a mýtus o Kristu, Karolinum, Prague 2007). The author approaches the subject from the perspective of religious studies, not theology, and suggests that the statement “Jesus has been resurrected” was preceded by a testimony that “God has exalted Jesus”. Likewise, the accounts of the resurrected Jesus’ appearances were preceded by im-minent expectations of Parousia, i. e. expectations that the crucified one would soon return and usherin the Kingdom he had announced. The author suggests that such visions were probably triggered and carried by the expression “Maranatha!”, meaning “Our teacher, come!”. The “Maranatha” formula played an unclear role in early Christianity and was probably adopted from the Qumran community, where it had been used to express expectations of the return ofthe Teacher of Righteousness. O. A. Funda has studied early Christianity for forty years. Between 1990 and 2010 he has taught philosophy and religious studies at the Charles University in Prague; now he is retired and is a guest lecturer at the University of West Bohemia in Pilsen